Peningkatan Keterampilan Membaca Siswa Melalui Model Literasi Based Learning pada Pembelajaran Bahasa - Sri Mulyani; M. Kadarin Jarnawi; Agus Shomad; Tholabi Tholabi; Atik Nurhidayati; Sri Widiastuti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Reading is one of the most essential language skills, as it serves numerous functions in human life. It is a key factor in determining students' academic success. This study employs a qualitative approach. The research subjects are teachers at Madrasah Tsanawiyah Negeri 1 Klaten, with language teachers serving as informants. Data collection techniques include interviews, observation, and documentation. The results of the study are as follows: 1) The steps of the Literacy-Based Learning model include: Contact stage – the teacher introduces relevant issues or problems; Curiosity stage – problems are presented in the form of questions that stimulate students’ curiosity and desire to learn; Elaboration stage – exploration, concept formation, and concept reinforcement are carried out; Decision-making stage – collaborative resolution of the issues presented; Nexus stage – students extract key ideas and materials learned; Assessment stage – evaluation focuses not only on knowledge but also on processes, context of application, and attitudes. 2) The advantages of the Literacy-Based Learning model are that it is enjoyable and student-friendly, Thereby fostering enthusiasm for learning; All students show empathy, care, and mutual respect; It nurtures curiosity and a love of knowledge; It enhances students’ communication skills and ability to contribute to the social environment. 3) The weaknesses of the Literacy-Based Learning model include misconceptions about reading competence among students and teachers; The learning process does not yet fully utilize instructional media; school teaching materials tend to focus on low-order thinking skills; and school facilities have not been optimally developed as a center for improving students’ reading abilities. The conclusion of this study is that the Literacy-Based Learning model has proven effective in improving reading skills in language.